Consumption and factors associating the provision of fruits and vegetables to children in Bayelsa state of Nigeria - Osunu, Patricia T.; Moyegbone, John E.; Ofili, Charles C.; Nwose, Ezekiel U. (International Journal of Research in Medical Sciences, 2024)
Background: The provision of adequate nutrition is of the utmost importance for the promotion of optimal growth and development in the early stages of human life as well as the stimulation of immune system function to combat infections. Therefore, this study aimed to assess the level of consumption and the factors affecting the provision of fruits and vegetables to children in Bayelsa state of Nigeria. Methods: This was a population-based survey conducted among 360 parents/caregivers of children aged 5 years and below randomly selected from Bayelsa state, Nigeria. The data for this study was collected with in-person interviews utilizing a standardized questionnaire. The results were presented in frequency and percentage. The level of significance was determined using a confidence interval of 95% and p<0.05. Results: Most of the respondents 355 (98.6%) were female with the age range 25-44 making 86.65% of the total population. Findings show that 40.8% of respondents gave their children fruits and vegetables only once a week while 3.6% gave their children fruits and vegetables 4 times and above a week. The majority of respondents 240 (66.7%) indicated that the high cost of fruits and vegetables was the main factor that affected consumption of fruits and vegetables. Conclusions: The findings demonstrated a low consumption level of fruits and vegetables among the children in Bayelsa state. Therefore, health professionals should be obliged to educate parents and caregivers of children on adequate provision of fruits and vegetables for their children.